Perancangan Sistem Pemanenan Air Hujan Skala Rumah Tangga untuk Pemenuhan Kebutuhan Air Bersih dan Konservasi Air Tanah - Aldi Ainun Habibi; Hari Siswoyo; Riyanto Haribowo (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
The problems that commonly occurred in the field of water resources were the lack of clean water in the dry season and excess water in the wet season. Those problems may impact on efforts to fulfil the need for clean water. One of the efforts that can be used to overcome those problems is rainwater harvesting. The purpose of this research was to design a rainwater harvesting system to fulfil the need for clean water during the dry season and groundwater conservation in the wet season. The design of the system includes the roof of the rainwater harvesting building, rainwater harvesting reservoirs, infiltration wells, and rainwater quality treatment equipment. The roof of the rainwater harvesting building was designed with a size of 6.50 m x 5.00 m. The runoff discharge from the roof is 1,084.02 liters/hour. The available rainwater harvesting reservoir has a capacity of 5,300 liters. There were 2 units of infiltration wells that function to absorb abundant rainwater from rainwater harvesting reservoirs, each well is 0.80 m in diameter and 1.35 m deep. Utilization of water from rainwater harvesting reservoirs can be done after going through the process in rainwater quality treatment equipment. The results of this activity can be recommended for widespread application.